Optimizing Organizational Performance : Exploring The Integration Of AI And HR Practices - Cahyatih Kumandang; Ruslaini Ruslaini; Seger Santoso; Muhammad Rizal (International Forum of Researchers and Lecturers, 2022)
In the rapidly evolving landscape of artificial intelligence (AI), optimizing human resources (HR) practices is imperative to foster organizational excellence. This qualitative research aims to explore the intersection of AI and HR practices to enhance organizational performance. The research adopts a qualitative approach utilizing in-depth interviews with HR professionals, AI specialists, and organizational leaders. Sampling techniques include purposive and snowball sampling to ensure diverse perspectives are captured. Data analysis involves thematic analysis, allowing for the identification of patterns and themes within the qualitative data. Preliminary findings indicate that organizations are increasingly leveraging AI to streamline HR processes, enhance talent acquisition, and improve employee engagement. Furthermore, the research reveals the significance of ethical considerations and human oversight in AI-driven HR practices. This study contributes to the growing discourse on AI integration in HR and provides insights for organizations aiming to navigate the AI-driven landscape while fostering excellence in HR practices.